A computational investigation of strain concentration in the brain in response to a rapid temperature rise. (March 2021) - Dagro, Amy; Wilkerson, Justin
Abstract: Following the mysterious health attacks on U.S. diplomats in Cuba in 2016, the cause of concussion-like symptoms concurrent with strange noises heard by the diplomats remains undetermined. A wide range of possible causes of the sensations have been proposed: pulsed microwave exposure, infrasound acoustic devices, pesticides/neurotoxins, and even mass hysteria (psychogenic illness). Here, we numerically examine the pulsed microwave exposure hypothesis and the simulated mechanical response of brain tissue. A computational model is used to examine the influence of various spatially varying temperature gradients and pulse durations on the mechanical response of brain tissue. We show that a stress-focusing effect due to a rapid temperature increase may result in brain tissue strains larger than the initially applied thermal strains.